The Analysis of Student Process Skills in Implementing Practicum on Straight Motion Material in High School - Sartika, Medya; Islami, Nur; Zuhdi, Zuhdi (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study aims to describe students skills in carrying out practicum on straight motion material in high school. This type of research is descriptive research supported by a quantitative approach while the method is survey. The sample in this study is class X IPA 1 and class X IPA 2 with a total of 67 students, the determination of the sample is done by purposive sampling.The data in this study in the form of scores of students skills in carrying out practicum on straight motion material in high school which were analyzed descriptively, scoring, tabulating and categorizing according to the category level of students process skills.. This research is seen from the aspects of preparation, implementation and closing. Based on the data analysis obtained the skill level in the preparation aspect gained a score of 3.35 with good category, the implementation aspect gained a score of 3.25 with a fairly good category and the closing aspect gained a score of 3.49 with a good score. Thus it can be concluded that students of class X IPA 1 and X IPA 2 in SMA Negeri 14 Pekanbaru have the skills to carry out practicum on good straight motion material.